Instagram - Amaral, Inês (2015)
Instagram is a location-based social network mobile application for sharing photos and videos. This service allows users to apply digital filters and share their photos and videos on other social networks and social media platforms. The service was founded by Kevin Systrom and Mike Krieger in San Francisco, California, and officially launched exclusively for the iPhone on October 6, 2010. The original name of the application was Burbn, which aimed to combine several characteristics of popular social media services like Foursquare. When Krieger joined the project, the two programmers decided to focus exclusively on photo sharing.